GAMBARAN PENGETAHUAN IBU NIFAS TENTANG MANFAAT PEMBERIAN COLOSTRUM PADA BAYI BARU LAHIR DI PUSKESMAS BAAMANG UNIT I SAMPIT - vina anggraini; Rini Lestari (Jurnal Ilmiah Kebidanan dan Kesehatan Wanita, 2019)
ABSTRACT Background : According to the Indonesian Pediatrician Association (IDAI Indonesia, the current infant mortality rate is 35 per 1,000 live births), not less than 10 babies and 20 children under five die every hour in Indonesia Mother's Milk (ASI) since time immemorial is believed to be the only main nutrients for newborns, as obtained from colostrum, namely breast milk produced during the first few days after birth. In April 2018 there were 60 postpartum mothers. Researchers interviewed 10 postpartum mothers as a sample who asked questions about the benefits of colostrum on newborns born from the results obtained by 7 mothers who did not give colostrum to their babies after birth, 3 mothers gave colostrum to their babies after giving birth. Objective: Knowing the description of postpartum mothers' knowledge about the benefits of colostrum in newborn at Baamang Health Center Unit I sampit Year 2018 based on age and work education. Methods: Descriptive study. This research was conducted at the Baamang Health Center Unit I sampit year 2018. The amount of samples in the study is about 20 respondents and using Acidental sampling. Results : Of the 20 postpartum women respondents, the majority of postpartum mothers knowledge abaot the benefits of knowledgeable colostrum is sufficient.The majority based on education 9 respondents (45%) based on the majority of 11 respondents (55%) based on the majority of 9 respondents (45%). Conclusion : The majority of postpartum mothers about the benefits of colostrum in health center baamang unit I sampt with sufficient knowledge. Keywords : Knowledge, maternal postpartum, Colostrum.